A Retrospective Study: Clinical Manifestation of Genital Herpes Infection - Laissa Bonita; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Genital herpes infection was sexual transmitted disease, caused by Herpes simplex virus (HSV) especially type 2. The characteristic of clinical sign is group of vesicles, based on eritematous macule, and often recurrent. Purpose: To evaluate the pattern of genital herpes patients at Sexual Transmitted Infection (STI) Division, Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya, since January 2011 until December 2015. Methods: A retrospective study took, data were obtained medical record of herpes simplex genitalis patients at STI Division, Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya, since January 2011 until December 2015. Results: The number of genital herpes infection cases decreased, 1.8% of patients who came to STI division Outpatient Clinic. Mostly women who were 25–34 years of age. Most common main complaints were pain. Erosion was the most clinical manifestation. The patients mostly got oral acyclovir and analgesic as the treatment. The majority of patient had counseling for about 55.9%. They came to be followed up at least once. Conclusion: The number of genital herpes cases decreased. The most of age affected were sexually active group.